"#houstonstrong": Resisting and reifying the neoliberal public. Issue 3 (September 2018) - Wingard, Jennifer
This article argues that during and after Hurricane Harvey, Houstonians used the hashtag #houstonstrong as a way of creating a public. This public functioned much in the ways defined by scholars as a means to forward collective action outside the confines of the state. Although it formed adjacent to state mandates, this public never agitated against state practices. Instead, #houstonstrong became not only a way to organize civilian and privatized rescue during the storm but also a point of pride for Houstonians and businesses across Houston. Therefore, I argue that even though #houstonstrong functioned as a traditional public in many ways, its adherence to neoliberal logics makes it a complex form of publicity that challenges the binary between traditional and neoliberal definitions of public behavior.